Representation learning for mammography mass lesion classification with convolutional neural networks. Issue 127 (April 2016) - Arevalo, John; González, Fabio A.; Ramos-Pollán, Raúl; Oliveira, Jose L.; Guevara Lopez, Miguel Angel
Abstract : Highlights: Innovative representation learning framework for breast cancer lesion classification. A hybrid CNN method to learn image-based features in a supervised way. New breast cancer benchmarking dataset to support computer-aided diagnosis methods. Abstract: Background and objective: The automatic classification of breast imaging lesions is currently an unsolved problem. This paper describes an innovative representation learning framework for breast cancer diagnosis in mammography that integrates deep learning techniques to automatically learn discriminative features avoiding the design of specific hand-crafted image-based feature detectors. Methods: A new biopsy proven benchmarking dataset was built from 344 breast cancer patients' cases containing a total of 736 film mammography (mediolateral oblique and craniocaudal) views, representative of manually segmented lesions associated with masses: 426 benign lesions and 310 malignant lesions. The developed method comprises two main stages: (i) preprocessing to enhance image details and (ii) supervised training for learning both the features and the breast imaging lesions classifier. In contrast to previous works, we adopt a hybrid approach where convolutional neural networks are used to learn the representation in a supervised way instead of designing particular descriptors to explain the content of mammography images. Results: Experimental results using the developed benchmarking breast cancer dataset demonstrated that our method exhibits significant improved performance when compared to state-of-the-art image descriptors, such as histogram of oriented gradients (HOG) and histogram of the gradient divergence (HGD), increasing the performance from 0.787 to 0.822 in terms of the area under the ROC curve (AUC). Interestingly, this model also outperforms a set of hand-crafted features that take advantage of additional information from segmentation by the radiologist. Finally, the combination of both representations, learned and hand-crafted, resulted in the best descriptor for mass lesion classification, obtaining 0.826 in the AUC score. Conclusions: A novel deep learning based framework to automatically address classification of breast mass lesions in mammography was developed.